Construction and Evaluation of Rodent-Specific rTMS Coils - Tang, Alexander D.; Lowe, Andrea S.; Garrett, Andrew R.; Woodward, Robert; Bennett, William; Canty, Alison J.; Garry, Michael I.; Hinder, Mark R.; Summers, Jeffery J.; Gersner, Roman; Rotenberg, Alexander; Thickbroom, Gary; et al. (Frontiers in Neural Circuits, 2016)
Rodent models of transcranial magnetic stimulation (TMS) play a crucial role in aiding the understanding of the cellular and molecular mechanisms underlying TMS induced plasticity. Rodent-specific TMS have previously been used to deliver focal stimulation at the cost of stimulus intensity (12mT). Here we describe two novel TMS coils designed to deliver repetitive TMS (rTMS) at greater stimulation intensities whilst maintaining spatial resolution. Two circular coils (8 mm outer diameter) were constructed with either an air or pure iron core. Peak magnetic field strength for the air and iron-cores were 90mT and 120mT respectively, with the iron-core coil exhibiting less focality. Coil temperature and magnetic field stability for the two coils undergoing rTMS, were similar at1Hz but varied at 10Hz. Finite element modelling of 10Hz rTMS with the iron-core in a simplified rat brain model suggests a peak electric field of 85 V/m and 12.7 V/m, within the skull and the brain respectively. Delivering 10Hz rTMS to the motor cortex of anaesthetised rats with the iron-core coil significantly increased motor evoked potential amplitudes immediately after stimulation (n=4). Our results suggest these novel coils generate modest magnetic and electric fields, capable of altering cortical excitability and provide an alternative method to investigate the mechanisms underlying rTMS-induced plasticity in an experimental setting.